2014
DOI: 10.1016/j.immuni.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Adult Thymus Contains FoxN1− Epithelial Stem Cells that Are Bipotent for Medullary and Cortical Thymic Epithelial Lineages

Abstract: SummaryWithin the thymus, two major thymic epithelial cell (TEC) subsets—cortical and medullary TECs—provide unique structural and functional niches for T cell development and establishment of central tolerance. Both lineages are believed to originate from a common progenitor cell, yet the cellular and molecular identity of these bipotent TEC progenitors/stem cells remains ill defined. Here we identify rare stromal cells in the murine adult thymus, which under low-attachment conditions formed spheres (termed “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 44 publications
3
115
1
1
Order By: Relevance
“…2 stem cells, and second, they are unable to rebuild the thymus after prenatal intoxication of Foxn1 + TECs (38,39). These cells may originate from the incomplete separation of the parathyroid and the thymus (40), as has been proposed previously for the cervical thymus in a reciprocal manner (21).…”
Section: Foxn1mentioning
confidence: 84%
“…2 stem cells, and second, they are unable to rebuild the thymus after prenatal intoxication of Foxn1 + TECs (38,39). These cells may originate from the incomplete separation of the parathyroid and the thymus (40), as has been proposed previously for the cervical thymus in a reciprocal manner (21).…”
Section: Foxn1mentioning
confidence: 84%
“…It is assumed that both mTECs and cTECs develop from common bi-potent thymic epithelial progenitors (TEPs) (Rossi et al, 2006), which remain incompletely characterized, particularly in the adult thymus (Ucar et al, 2014; Wong et al, 2014). However, more recent studies have also suggested the existence of mTEC lineage-specific progenitors/stem cells in both embryonic (Sekai et al, 2014) and adult thymus (Ohigashi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified this progenitor cell population using different methods (Fig. ) . One research group identified this progenitor cell line by identifying a rare cell population derived from adult mouse thymic stromal cells that formed thymospheres, a property of progenitor cells.…”
Section: New Insights Into Mtec Development and Turnovermentioning
confidence: 99%